2020
DOI: 10.1002/jdd.12192
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from the Health Resources and Services Administration's Dental Faculty Development Program

Abstract: Purpose/objectives While the Commission on Dental Accreditation (CODA) requires programs to conduct faculty development, implementation of faculty development activities vary widely. Faculty development programs can enhance teaching, research, and leadership skills needed to transition from clinical practice to teaching. In 2012, the Health Resources and Services Administration (HRSA) funded 6 institutions to plan, develop, and operate programs for training oral healthcare providers who plan to teach in genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Faculty development programs have been found to be extremely beneficial across health professions 27 and necessary in dental education 28 . Participation in long‐term faculty development programs increases leadership confidence, engagement, collaboration and contributes to increased productivity 29,30 . In addition, supporting junior faculty members in the development of their faculty identity as well as provide mentorship and general support can contribute to faculty retention 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faculty development programs have been found to be extremely beneficial across health professions 27 and necessary in dental education 28 . Participation in long‐term faculty development programs increases leadership confidence, engagement, collaboration and contributes to increased productivity 29,30 . In addition, supporting junior faculty members in the development of their faculty identity as well as provide mentorship and general support can contribute to faculty retention 31 .…”
Section: Discussionmentioning
confidence: 99%
“…28 Participation in long-term faculty development programs increases leadership confidence, engagement, collaboration and contributes to increased productivity. 29,30 In addition, supporting junior faculty members in the development of their faculty identity as well as provide mentorship and general support can contribute to faculty retention. 31 However, in 2016, less than half of US and Canadian dental schools had an Office of Faculty Affairs or Faculty Development, and sustained financial support for professional development activities is, generally, limited.…”
Section: Offices For Faculty Development and Faculty Affairsmentioning
confidence: 99%
“…3-11. Such support to the faculty results in a positive change in their teaching behaviours and they contribute in their institutions by escalating the quality of teaching programs. [12][13][14][15][16][17] This study showed that majority of participants had not received any type of faculty development training as represented by the data for both modes of delivery. In addition, the participants who received the training offered by the institution or elsewhere, increased the prospect of developing and improving the skills of educational administration and teaching.…”
Section: Discussionmentioning
confidence: 79%
“…16,17,34 These patient-level factors, in conjunction with the aforementioned provider-level factors, suggest a significant barrier to accessing timely dental care for pregnant women. There has been increased attention to encourage ANC providers in oral health promotion in various healthcare settings across Australia 31 and around the world, 35 with studies demonstrating such programmes are feasible and effective. 15,36,37 More pragmatic options for preventative dental care among Tasmanian pregnant women, such as through streamlined referral processes by ANC providers to local dentists and a trained, oral health-informed medical workforce, are recommended.…”
Section: Discussionmentioning
confidence: 99%